The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.4018/978-1-5225-2639-1.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Educational Software Design

Abstract: Educational software is somewhat unique in that the goal of the software is not to facilitate use of the software itself, but to produce an impact on the user - learning - that will affect the user's behavior outside of the software. Although there are many areas where educational software designers can learn from practices in productivity and game design, there are reasons to be cautious in applying such principles to educational software. This chapter considers several design elements in educational software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It further encouraged students to self-learn, exchange ideas, and integrate into learning through digital platform environments. Ritter et al (2018) confirmed that educational programs offered by universities did not help students to engage and integrate them (Ritter et al, 2018). The reason for this was that the educational software template was similar to the educational book template in terms of showing chapters, lessons, and activities to students.…”
Section: Introductionmentioning
confidence: 90%
“…It further encouraged students to self-learn, exchange ideas, and integrate into learning through digital platform environments. Ritter et al (2018) confirmed that educational programs offered by universities did not help students to engage and integrate them (Ritter et al, 2018). The reason for this was that the educational software template was similar to the educational book template in terms of showing chapters, lessons, and activities to students.…”
Section: Introductionmentioning
confidence: 90%